The Contextuality of Tafsir Ma'ālim al-Tanzīl by al-Baghawī (Revisiting Tradition and Embracing Modern Values) - Riki Noviandi; Muhammad Naufal Hakim; Masruchan Masruchan; Mokh. Fatkhur Rokhman (Jurnal Semiotika Quran, 2024)
This research is conducted based on two facts: (1) the bias of modern-period commentators who tend to stigmatize classical exegesis as being subjective to schools of thought and scholarship, leading to the emergence of the concept of the Qur'an as guidance; (2) it is found that the concept of the Quran as guidance has been mentioned by classical commentators, as articulated by al-Baghawī in the introduction to his exegesis. Therefore, this research aims to offer a counter-narrative to the “negative stigma” against classical exegesis, perceived as non-contextual, by focusing on al-Baghawī’s Ma‘ālim al-Tanzīl as the subject matter. Employing a philosophical approach, the characteristic theory of Fahd al-Rūmī’s exegesis, and a critical-analytical method, this research concludes that Ma‘ālim al-Tanzīl exhibits characteristics through the use of the ma’thūr exegesis method, firmly rooted in the tradition of early interpretation, namely interpreting the Quran with the Quran, with Hadith, with the sayings of the Companions (Ṣaḥabī), and with the sayings of the Successors (Tābi‘īn). In addition to being based on narration, this exegesis also draws interpretations from the various recitations of the Quran and analyses of Arabic sciences. Although adhering to tradition, the contextual relevance of Ma‘ālim al-Tanzīl exegesis does not lie in directly addressing contemporary issues but rather in the revelation of morally universal values that remain pertinent to the current context.